2017
DOI: 10.1371/journal.pone.0189510
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cellular complexity of anoxygenic phototrophic sulfur bacteria in the chemocline of meromictic Lake Cadagno

Abstract: The meromictic Lake Cadagno is characterized by a compact chemocline with high concentrations of anoxygenic phototrophic purple sulfur bacteria (PSB) and green sulfur bacteria (GSB). The co-occurrence of phylogenetically distant bacterial groups such as PSB and GSB in the same ecological niche, makes the chemocline of Lake Cadagno an ideal system for studying the conditions and consequences of coexistence of photosynthetic bacteria populations. In this study, we applied flow cytometry (FCM) as a fast tool to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 56 publications
2
44
0
Order By: Relevance
“…To complete the photosynthetic water column analysis and to evidence possible microbial interactions between different lake compartments, FCM was applied as a rapid tool to detect photosynthetic microorganisms signature, as demonstrated in earlier studies [27,36,37]. Our FCM analyses of phototrophic microbial populations revealed unexpected yearly dynamics in community composition with possible effects on water column stability (Fig 5).…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…To complete the photosynthetic water column analysis and to evidence possible microbial interactions between different lake compartments, FCM was applied as a rapid tool to detect photosynthetic microorganisms signature, as demonstrated in earlier studies [27,36,37]. Our FCM analyses of phototrophic microbial populations revealed unexpected yearly dynamics in community composition with possible effects on water column stability (Fig 5).…”
Section: Discussionmentioning
confidence: 63%
“…It has been suggested that reduced incident light towards the end of the vegetative period favor the growth of large-celled PSB over that of small-celled PSB [55]. However, that study and a companion study [27] suggest that microbial community dynamics in Lake Cadagno might be strongly influenced by intra- and interspecific interactions.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations